IMPLEMENTATION OF E-GOVERNMENT THROUGH THE SIDOARJO PEOPLE'S SERVICE SYSTEM (SIPRAJA) IN SIDOKERTO VILLAGE, BUDURAN DISTRICT, SIDOARJO REGENCY - Ahzana, Irma Fa'ada; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The use of information technology in public services represents a strategic initiative in bureaucratic reform, and the Sidoarjo Regency Government has introduced the SIPRAJA (Sidoarjo People’s Service System) application as an e-government innovation to enhance service quality. This study aims to examine the implementation of the SIPRAJA application in Sidokerto Village, Buduran District, Sidoarjo Regency, and to analyze the factors influencing its effectiveness. Method: A qualitative descriptive approach was employed with purposive sampling to determine research subjects, focusing on the Sidokerto Village Hall as the research locus. Data were collected through observation, interviews, and documentation, and analyzed using Edward III’s policy implementation indicators. Results: The findings reveal that SIPRAJA implementation in Sidokerto Village is relatively effective, with two-way communication established between the government and community, although challenges persist among elderly users. Human resources and infrastructure are generally adequate, yet limitations such as the absence of dedicated computers and recurring technical issues remain. The implementers demonstrate positive attitudes, and bureaucratic structures are functional but lack specific SOPs for SIPRAJA operations. Novelty: This research contributes by highlighting the practical challenges of e-government implementation at the village level and emphasizing the urgency of both technical and administrative improvements to optimize digital public services